Substratum morphology and significance during the Weichselian Odra ice lobe advance in northeast Germany and northwest Poland - Hermanowski, Piotr (Geologos, 2015)
In the Polish Lowlands, three main ice lobes, referred to as Odra, Vistula and Mazury, formed during the Last Scandinavian Glaciation. These lobes protruded at least several kilometres beyond the main ice margin and it is believed that they represent terminal parts of the ice streams. Applied geostatistical analysis based on numerous geological data has allowed an approximate reconstruction of the Odra ice lobe substratum in the area of northwest Poland and northeast Germany. A spatial representation of the Odra lobe substratum clearly illustrates the adverse slope of the glacier bed, but also indicates areas morphologically prone to ice streaming. It is suggested that the ice took advantage of local topography that enabled advance out of the Baltic basin; consequently, the ice followed a topographic low which, in combination with favourable hydraulic conditions of its substratum, likely initiated ice streaming.